2015
DOI: 10.5664/jcsm.4940
|View full text |Cite
|
Sign up to set email alerts
|

Altered Sleep Stage Transitions of REM Sleep: A Novel and Stable Biomarker of Narcolepsy

Abstract: EDS, such as obstructive sleep apnea syndrome (OSAS), 5,6 behaviorally induced insuffi cient sleep syndrome (BIISS), 7 and sleep interruption, 8 can also show similar diagnostic features of narcolepsy on MSLT. It was found that 3.9% to 17% of the general population had multiple SOREMPs, 9,10 and 3.6% could meet the MSLT diagnostic criteria of narcolepsy.11 In other words, the MSLT criteria of ICSD-3 would likely give rise to a high false positive rate in diagnosing narcolepsy. BRIEF SUMMARYCurrent Knowledge/St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 30 publications
4
14
0
Order By: Relevance
“…A decreased N2 to REM sleep transition feature was also found to be specific for narcolepsy (data not shown), but as it inversely correlated with the SOREMPs at night transition feature and was less predictive, it was not pursued. This is in accordance with the findings of Liu et al [23] who found altered transition from N2/N3 sleep to REM sleep in narcolepsy types 1 and 2 compared with unaffected relatives and controls. By combining sleep variables in a decision tree, they enhanced the sensitivity and specificity of diagnosing narcolepsy types 1 and 2, but they found that the transition measures computed from MSLT were more indicative than those computed from nocturnal PSGs [23].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A decreased N2 to REM sleep transition feature was also found to be specific for narcolepsy (data not shown), but as it inversely correlated with the SOREMPs at night transition feature and was less predictive, it was not pursued. This is in accordance with the findings of Liu et al [23] who found altered transition from N2/N3 sleep to REM sleep in narcolepsy types 1 and 2 compared with unaffected relatives and controls. By combining sleep variables in a decision tree, they enhanced the sensitivity and specificity of diagnosing narcolepsy types 1 and 2, but they found that the transition measures computed from MSLT were more indicative than those computed from nocturnal PSGs [23].…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with the findings of Liu et al [23] who found altered transition from N2/N3 sleep to REM sleep in narcolepsy types 1 and 2 compared with unaffected relatives and controls. By combining sleep variables in a decision tree, they enhanced the sensitivity and specificity of diagnosing narcolepsy types 1 and 2, but they found that the transition measures computed from MSLT were more indicative than those computed from nocturnal PSGs [23]. However, they did not include a confirmation sample, and it is therefore unclear how their decision tree would perform in a clinical setting.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consequently, patients with N-1 often complain of (in addition to cataplexy) disrupted sleep/wake continuity and often display abnormal sleep architecture upon laboratory study. For example, several studies have shown that, compared to controls, N-1 is associated with reduced sleep efficiency, increased wake after sleep onset (WASO), high arousal indices, frequent sleep stage transitions, increased time in “light” sleep (Sorensen et al, 2013, Pizza et al, 2015, Mukai et al, 2003, Khatami et al, 2008, Jiménez-Correa et al, 2009, Frauscher et al, 2011; Roth et al, 2013) and abnormal REM sequencing (Liu et al, 2015, Drakatos et al, 2016). It is also well-documented that N-1 patients have a shortened latency to nocturnal REM, now known to be statistically specific for low or absent hypocretin (Andlauer et al, 2013, Reiter et al, 2015; Cairns and Bogan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative analyses elucidate high-resolution temporal changes in electroencephalogram (EEG) frequency population that are not adequately reflected using traditional scoring methods (Achermann, 2009). Existing literature on narcolepsy using quantitative analyses suggests impairments in both slow wave activity (SWA) and REM sleep processes including altered REM sequencing (Liu et al, 2015, Drakatos et al, 2016), attenuated circadian organization of REM (Mukai et al, 2003), and potentially hyper-sensitive homeostatic regulation of SWA (Khatami et al, 2008, Khatami et al, 2007, Yun et al, 2017). However, the majority of research has been conducted on narcolepsy with confirmed low or absent hypocretin, and very little is known about the regulation of nocturnal sleep in other hypersomnias, including N-2 and IH.…”
Section: Introductionmentioning
confidence: 99%